2021
DOI: 10.1007/s10653-021-00950-x
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and microbiological characteristics of urban aerosols in Krakow (Poland) and their potential health impact

Abstract: Eight aerosol samples were collected in Krakow using a low-volume sampler in February and March 2019 during variable meteorological conditions and times of the day, to study their single particles’ properties (size, morphology and chemical composition analyzed using a scanning electron microscope fitted with an energy-dispersive spectrometer) and microbiological characteristics. The content of particles of different chemical compositions larger than 2.5 μm was low. Considering the number of the particles, subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…People living in urban areas are at a greater risk of harmful effects resulting from air pollution. Epidemiological studies have shown adverse associations between exposure to high particulate matter concentration and human health [1][2][3] as well as they have revealed that there exists a link between the mortality rate increase and presence of smog [4][5][6]. Although between 2000 and 2010 the PM10 concentration generally decreased in Central Europe due to changes in meteorological conditions such as higher wind speeds or warmer winters, the PM10 concentration in Poland STILL exceeds the standards set by the European Union and World Health Organization (WHO).…”
Section: Introductionmentioning
confidence: 99%
“…People living in urban areas are at a greater risk of harmful effects resulting from air pollution. Epidemiological studies have shown adverse associations between exposure to high particulate matter concentration and human health [1][2][3] as well as they have revealed that there exists a link between the mortality rate increase and presence of smog [4][5][6]. Although between 2000 and 2010 the PM10 concentration generally decreased in Central Europe due to changes in meteorological conditions such as higher wind speeds or warmer winters, the PM10 concentration in Poland STILL exceeds the standards set by the European Union and World Health Organization (WHO).…”
Section: Introductionmentioning
confidence: 99%
“…The main airborne aluminum source is human industrial activity [59], and also, even though rarely in a temperate climate, wind-transported soil particles. Aluminum salts detected in the samples are rarely present among air pollutants in Krakow [60]. Aluminum salts, among others, were previously detected as present in the form of particulate matter in the so-called 'personal cloud' [61].…”
Section: Sem Observations and Microanalysis Of The Airborne Mp Fibres...mentioning
confidence: 97%
“…The identification of soot (in various aggregates) also relies upon the morphology of particles. Tar balls are often identified using their morphology determined in SEM studies (without verification of their internal structure using a transmission electron microscope, TEM) [43][44][45][46]. We include soot and tar balls among anthropogenic particles since significant emissions of these particles originate from fuel combustion processes (while we are aware they may also originate from wildfires).…”
Section: Atmospheric Pm Single-particle Analysismentioning
confidence: 99%